The Age‐Well observational study on expert meditators in the Medit‐Ageing European project. Issue 1 (8th December 2018) - Lutz, Antoine; Klimecki, Olga M.; Collette, Fabienne; Poisnel, Géraldine; Arenaza‐Urquijo, Eider; Marchant, Natalie L.; De La Sayette, Vincent; Rauchs, Géraldine; Salmon, Eric; Vuilleumier, Patrick; Frison, Eric; Vivien, Denis; et al.
Abstract: Introduction: The Age‐Well observational, cross‐sectional study investigates the affective and cognitive mechanisms of meditation expertise with behavioral, neuroimaging, sleep, and biological measures sensitive to aging and Alzheimer's disease (AD). Methods: Thirty cognitively unimpaired individuals aged 65 years or older with at least 10, 000 hours of practice in mindfulness meditation (MM) and loving‐kindness and compassion meditation (LKCM) are selected. The outcomes are the neuroimaging brain correlates of MM and LKCM and the assessments of long‐term meditation practices on behavioral, neural, and biological measures as compared to nonmeditator older controls from the Age‐Well randomized controlled trial. Results: Recruitment and data collection began in late 2016 and will be completed by late 2019. Discussion: Results are expected to foster the understanding of the effects of meditation expertise on aging and of the mechanisms of action underlying the meditation intervention in the Age‐Well randomized controlled trial. These finding will contribute to the design of meditation‐based prevention randomized controlled trials for the aged population and to the exploration of the possible long‐time developmental trajectory of meditation training. Highlights: Age‐Well cross‐sectional study includes 30 elderly expert meditators (≥65 years old). Long‐term meditation practice could be linked to well‐preserved brain structure and function in aging. Long‐term meditation practice could be linked to health and well‐being in aging. Identifying novel markers of meditation expertise in older adults. Comparison of the impacts of mindfulness and compassion meditations on brain, cognitive, and emotional processes in elderly expert meditators.